2017
DOI: 10.1016/j.ajog.2016.11.1006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcomes associated with early preterm cesarean delivery

Abstract: Background Data on complications associated with classical cesarean delivery are conflicting. In extremely preterm cesarean delivery (22 0/7–27 6/7 weeks’ gestation), the lower uterine segment is thicker. It is plausible that the rates of maternal complications may not differ between classical and low transverse cesarean. Objective To compare maternal outcomes associated with classical comparing with low transverse cesarean after stratifying by gestation (23 0/7–27 6/7 and 28 0/7–31 6/7 weeks’ gestation). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Cesarean section (63%) was much more common than vaginal delivery (37%) in our cohort, consistent with other studies of periviable infants that have found a prevalence of cesarean sections between 59 and 64% [5,7]. With more interventions, and higher survival of periviable infants over time, cesarean delivery of periviable infants is becoming more common [30][31][32]. Some studies support the idea that delivery via cesarean section may provide benefits for the most immature infants, delivered at 22-25 weeks of gestation, independent of maternal risk factors for cesarean section [33][34][35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cesarean section (63%) was much more common than vaginal delivery (37%) in our cohort, consistent with other studies of periviable infants that have found a prevalence of cesarean sections between 59 and 64% [5,7]. With more interventions, and higher survival of periviable infants over time, cesarean delivery of periviable infants is becoming more common [30][31][32]. Some studies support the idea that delivery via cesarean section may provide benefits for the most immature infants, delivered at 22-25 weeks of gestation, independent of maternal risk factors for cesarean section [33][34][35].…”
Section: Discussionsupporting
confidence: 89%
“…Some studies support the idea that delivery via cesarean section may provide benefits for the most immature infants, delivered at 22-25 weeks of gestation, independent of maternal risk factors for cesarean section [33][34][35]. However, in one recent study of cesarean sections done at this early GA, almost one in four women experienced a serious maternal complication, regardless of incision type [32]. There have been no randomized controlled trials comparing cesarean delivery with vaginal delivery in the periviable period.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that maternal Position of the first fetus for the multiple pregnancies. complications did not differ according to whether women had classical or low-transverse incisions between 23 and 28 weeks of gestation (18). Women in the two groups had significantly different obstetric diseases, with more chorioamnionitis in those at 24-25 weeks and more fetal growth restriction in those at 26-27 weeks.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Kawakita et al studied maternal complications according to type of uterine incision and stratified by gestational age. They showed that maternal complications did not differ according to whether women had classical or low‐transverse incisions between 23 and 28 weeks of gestation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation